Pengaruh Kualitas GCG, Ukuran Bank dan BOPO terhadap Fraud pada BPD di Sumatera Periode 2017-2024 - Fasha, Muhammad Ananda Islami; Matoati, Rindang; Purwanto, Budi; Viana, Eka Dasra (IPB University, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG) quality, bank size, and the operating expenses to operating income ratio (BOPO) on the frequency of fraud at Regional Development Banks (BPD) in Sumatra during the 2017–2024 period. The main problem addressed is the high risk of fraud in BPDs, which threatens operational stability and public trust. This research employs a quantitative approach using secondary data obtained from annual reports and GCG self-assessment reports. Panel data regression with the Random Effect Model was used for analysis. The results show that bank size has a positive and significant effect on fraud at the 10% level (p = 0.085), while BOPO also has a positive and significant effect at the 10% level (p = 0.062). Meanwhile, GCG quality has a negative but statistically insignificant effect (p = 0.439). These findings indicate that increasing bank size and lower operational efficiency tend to elevate fraud risk, whereas improvements in GCG have not yet shown a significant impact on reducing fraud. The study highlights the importance of improving operational efficiency and strengthening oversight in large BPDs to mitigate fraud risks in regional financial institutions.